Susceptibility of Campylobacter pyloridis to 20 antimicrobial agents. - Lambert, T (1986)
The susceptibility of 50 strains of Campylobacter pyloridis, isolated from human gastric biopsies, to 20 antimicrobial agents representing the different families of antibiotics was tested. The pattern of susceptibility was similar to that of the C. jejuni-C. coli group except for ampicillin, cephalothin, and rifampin. The relative resistance to cefsulodin was also noted.